Three new species of Caponiid spiders from Ecuador (Araneae, Caponiidae) - Dupérré, Nadine (Zootaxa, 2014)
Three new species of Caponiidae in two different genera are described from Ecuador. Nops cesari n. sp., Nops quito n. sp. and Nyetnops juchuy n. sp. A key to the genera of the subfamily Nopinae is provided.